Konflik Internal Multikulturalisme dalam Film Good Bye Lennin! - Nurfaidah, Resti (Paradigma: Jurnal Kajian Budaya, 2015)
Germany is one of several countries in the world that has ever been upside-down in historical experience. A long history proved that Germany was used to be a union. But unfortunately it had split based on ideological differences. Though was originating from same ancestors, language, culture, it was fallen into an extreme internal multicultural conflict as proved by the establishment of the wall. During these period, a long history of human relations in both German were well recorded. Besides, it was taken as insprirations in many literary or artistic works, including films. One of the films telling the period between pre and post reunification is Wolfgang Becker’s Good Bye Lennin! (2003). This study focuses on the internal multicultural conflict founded in a country which has the same culture split by different integral ideology--later by its reunion. Based on several concepts of multiculturalism, the result of this study indicates that figures of the film have internal multiculturalisme conflict that raise multicultural shocks and resistances in the change of Germany political situation.